1978
DOI: 10.1179/bjo.5.4.183
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of some Features of the Indonesian Occlusion with those of two other Ethnic Groups

Abstract: A sample of 184 randomly selected Indonesian children aged from 7 to 13 years from Surabaya, Java was examined for the prevalence of dental malocclusion. The examination was supported by cephalometric and photographic records and dental casts. Results showed a high prevalence of incisor crowding, bimaxillary prognathism, and a class I molar relationship. While crowding was very common, there appeared to be few antero-posterior, vertical or lateral discrepancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 3 publications
1
16
0
Order By: Relevance
“…Class III patients with long faces are widespread in Asia [2,29]. In our research, the FMA angle was substantially correlated with lower LCF (Table 3, P < 0.001).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Class III patients with long faces are widespread in Asia [2,29]. In our research, the FMA angle was substantially correlated with lower LCF (Table 3, P < 0.001).…”
Section: Discussionsupporting
confidence: 58%
“…Kitai [1] reported that 5-20% of the Japanese population possessed the characteristics of Class III malocclusion. Similarly, Johnson [2] discovered a prevalence of 23% in Chinese children.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several studies investigating the prevalence of various dentofacial characteristics in different populations [1][2][3][4][5][6][7] but only a few have been conducted on an orthodontic population. [8][9][10][11][12][13] The aim of the study was to provide quantitative information regarding the pattern of dentofacial characteristics in orthodontic patients and to find the frequencies of Angle's classes and other dentofacial characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 One study by Smith et al 1 showed that midface fractures are frequently present in the orbit (32%), malar bone and maxilla (26%), and the nasal bones (19%). 1 Another study done by Hwang and You 3 stated the most common isolated fracture site was the nasal bone (37.7%), followed by the mandible (30%), orbital bones (7.6%), zygoma (5.7%), maxilla (1.3%), and the frontal bone (0.3%). The most common etiology was violent assault or nonviolent traumatic injury (49.4%).…”
mentioning
confidence: 97%
“…1 Mandibular prognathism is the most common reason for orthognathic treatment and orthognathic surgery in Asian countries. The socioeconomic status has developed, and the demand for not only a satisfying functional occlusion but also aesthetic needs has increased greatly over a short period.…”
mentioning
confidence: 99%